2013
DOI: 10.1159/000346515
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Invaginations in Bacteria and Mitochondria: Common Features and Evolutionary Scenarios

Abstract: Nonphotosynthetic bacteria generally lack intracellular membranes (ICMs). However, large scale overproduction of membrane proteins in Escherichia coli can be accompanied by a massive proliferation of new ICMs in the cytoplasm. In some cases, like in the overexpression of the ATP synthase b subunit in E. coli, the morphology of these internal invaginations resembles that of the inner mitochondrial cristae. Moreover, the new ICMs have a higher content in cardiolipin than the bacterial inner and outer membranes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 90 publications
(118 reference statements)
3
16
0
Order By: Relevance
“…The invaginations of the CM found in cells incubated in NBW, NSW and LB ON incubations may be the result of an increase in protein content relative to the lipid membrane. A similar mechanism has previously been reported in cells that overproduce membrane proteins [38][39][40]. The low level of OPGs in the periplasm of NFW VBNC cells may weaken their osmoprotection and prevent the formation of invaginations as the CM might be more strained through increased turgor pressure.…”
Section: Discussionsupporting
confidence: 70%
“…The invaginations of the CM found in cells incubated in NBW, NSW and LB ON incubations may be the result of an increase in protein content relative to the lipid membrane. A similar mechanism has previously been reported in cells that overproduce membrane proteins [38][39][40]. The low level of OPGs in the periplasm of NFW VBNC cells may weaken their osmoprotection and prevent the formation of invaginations as the CM might be more strained through increased turgor pressure.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, an increased and constant level of CL in mitochondria produced a different topology product of the non-bilayer properties of this phospholipid [54]. To support this view, recent evidence has demonstrated that liposomes containing the same composition of mitochondrial membranes are responsive to local pH gradients producing invaginations similar to those observed in the mitochondrial cristae.…”
Section: Discussionmentioning
confidence: 93%
“…Studies suggest that mitochondria share with bacteria several similarities . Both bacteria and mitochondria can consume O 2 and produce CO 2 , express formylated peptides and bear a circular genome composed of hypomethylated CpG DNA motifs .…”
Section: Mitochondria and Inflammationmentioning
confidence: 99%